2019
DOI: 10.1136/bmjopen-2019-033239
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study to investigate the burden and transmission of acute gastroenteritis in care homes: epidemiological results

Abstract: ObjectivesTo estimate the incidence of gastroenteritis in individuals in care homes.DesignProspective cohort study.SettingFive participating care homes in North West England, UK.ParticipantsResidents and staff present at the five study care homes between 15 August 2017 and 30 May 2019 (n=268).Outcome measuresWe calculated incidence rates for all gastroenteritis cases per 1000 person-years at risk and per 1000 bed-days at risk. We also calculated the incidence rate of gastroenteritis outbreaks per 100 care home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The incidence rate of norovirus-related diarrhea in the present study subjects was much lower than that previously reported in a prospective cohort study at care homes in England, which found an incidence rate of 225.2 per 1000 person-years. 20 Although the incidences vary according to the study season, location and population, the difference between studies can partly be explained by the following three reasons. First, epidemics of infectious gastroenteritis in the community were low during the study seasons, 21 which would have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of norovirus-related diarrhea in the present study subjects was much lower than that previously reported in a prospective cohort study at care homes in England, which found an incidence rate of 225.2 per 1000 person-years. 20 Although the incidences vary according to the study season, location and population, the difference between studies can partly be explained by the following three reasons. First, epidemics of infectious gastroenteritis in the community were low during the study seasons, 21 which would have affected our results.…”
Section: Discussionmentioning
confidence: 99%